Influencia de la superstición en el rendimiento deportivo de un equipo profesional de fútbol de Colombia: un estudio de caso (2019)
This research-study of case, it has as intention to understand the influence that has the superstition and the religious rituals, restored by a spiritual leader, on the sports performance of a professional soccer team. To carry out the development of this article a qualitative investigation of type was realized and there was made an analysis of the narratives and conducts, of the principal players of the sports equipment and of the spiritual leader, by means of radial interviews and a documentary, which were transcribed to be able to analyze what words were used more in every speech using a generator of clouds; then there were correlated this wordswith the card of acceptance or rejection of the superstition of De Miguel et al., (2012). It was found that the superstitious conducts generate an increase of the confidence, product of the causal relation that the sportsmen do between the realized rituals and the victories obtained immediately later. There was identified, in addition, that on having considered this situation to be real, implements a sensation of control on the circumstances, which produces an increase of the motivation to the moment to compete.